Determination of dimethoate pesticide residues in water in the environment surrounding Lake Al-Sin - عقده ديما; إبراهيم عزيز صقر; طارق عراج عراج (Latakia University Journal -Basic Sciences Series, 2023)
The unreasonable use of agrochemicals in the environment of the Lake Al-Sin Basin, and various human activities may predispose the water to pollution, especially with widely used organophosphate pesticides, which have an effect on the nervous system. The research sought to determine the concentration dimethoate of the synthetic organophosphate pesticide in the waters of the environment surrounding Lake Al-Sin. A questionnaire form was dispensation to the residents of the area, to determine the status of the studied area Ground and surface water samples were taken from several locations surrounding Lake Al-Sin. The study lasted for seven consecutive months, during which the different parameters (pH-EC-TDS-COD-PO4-3) were measured. The analysis of the pesticide was using a High Performance Liquid Chromatography (HPLC). The results showed the presence of dimethoate residues in the studied water samples with average concentrations ranging between (0.2-0.6) µg.l-1 were mostly higher than the recommended value for individual pesticide in water (0.1) µg.l-1 as recommended by the European Economic Commission. Consequently the observed was contamination of ground and surface waters with dimethoate in the studied sites, because of its much use, and because of its high solubility in water, it was also observed that concentration dimethoate increased with lower pH.